Modulation of Peripheral Immune Cell Subpopulations After RapidArc/Moderate Hypofractionated Radiotherapy for Localized Prostate Cancer: Findings and Comparison With 3D Conformal/Conventional Fractionation Treatment - D’Auria, Fiorella; Statuto, Teodora; Rago, Luciana; Montagna, Antonietta; Castaldo, Giovanni; Schirò, Irene; Zeccola, Anna; Virgilio, Teresa; Bianchino, Gabriella; Traficante, Antonio; Sgambato, Alessandro; Fusco, Vincenzo; et al. (Frontiers in Oncology, 2022)
Radiotherapy (RT) is an important therapeutic option in patients with localized prostate cancer (PC). Unfortunately, radiation treatment causes a decrease of peripheral lymphocytes and, consequently, influences the patients’ immune status. Our aim was to study changes of peripheral blood immune cell subpopulations after RT, and during 6 months follow up, in 2 groups of PC patients irradiated with different techniques and dose-fractions with curative intent. We investigated also the presence of correlation between immune cells modulation and genitourinary or gastrointestinal toxicity. We enrolled 44 patients treated with curative RT (RapidArc/hypofractionation regimen or 3D-conformal/conventional fractionation) for localized prostate cancer. Total white blood cell (WBC), absolute lymphocyte counts (ALC) and peripheral immune cell subpopulations were analyzed at baseline, at the end of RT and 3 and 6 months after the end of RT. WBC and ALC greatly decreased at the end of RT with a trend to recover at 6 months follow up in hypofractionation group but not in conventional one. Furthermore, B, total T, T CD4+, T CD8+ and NK cell values dropped significantly in both groups at the end of RT, with minor decrease detectable in hypofractionation group for B, total T and T CD4+ lymphocytes respect to the other technique/fractionation group. Double-negative T (DNT), double-positive T (DPT) and NKT cells significantly decreased at the end of RT with slight tendency to recover values during follow up, particularly in the hypofractionation group. No correlation with genitourinary or gastrointestinal toxicity was found. In this study, we showed, for the first time, the effects of RapidArc/moderate hypofractionation RT on immune cell subsets in patients treated for localized prostate cancer. Due to the growing interest in minority T cell subpopulations for immunotherapy, we reported also, never studied before, a longitudinal monitoring of the RT effects on DNT, DPT and NKT. Our preliminary data highlight the importance of considering the effects of different RT techniques/fractionation regimens on peripheral immune cells, in the era of RT and immunotherapy combination.